Metabolic Disruptions in Serum Calcium and Phosphate Levels Among Pre-Diabetic and Type 2 Diabetic Patients: Serum Calcium and Phosphate Levels in Diabetes Mellitus - Qazi, Abroo Fatima; Rahman, Najeeb ur; Mushtaq, Saira; Anis, Roomisa; Mahmud, Mahvesh; Pervaiz, Mudasar (Pakistan Journal of Health Sciences, 2024)
Diabetes mellitus is a metabolic disorder classified by persistently raised blood sugar levels. Objective: To identify diabetes mellitus disturbances in serum calcium and phosphate levels. However, the exact mechanisms underlying this association were not fully understood. Methods: It was a cross sectional study. It was conducted at Isra University Hospital, Hyderabad from March 2023 to August 2023. 170 patients were selected with 85 patients in each group. Group A included patients with diabetes and Group B included patients with prediabetes with fasting blood glucose levels of 101-125 mg/dl or HbA1c levels of 5.7-6.4%. Fasting blood glucose levels, HbA1c levels, total serum calcium levels and serum phosphate levels were compared. Data were assessed by using SPSS version 24.0. P-values of ≤0.05 will be statistically significant. Results: This study has shown that in both in Group A and Group B, the mean age was 47.2 ± 8.4 years and 48.5 ± 7.6 respectively (p value=0.62). Group A exhibited a mean fasting plasma glucose level of 109.34 mg/dl ± 17.92 and Group B 140.59 mg/dl ± 31.03. Group A displayed a mean serum phosphate level of 3.79 mg/dl ± 1.31, while Group B exhibited mean level of 4.43 mg/dl ± 1.04 (p=0.03). Group A demonstrated a mean serum calcium level of 8.41 mg/dl ± 1.03, whereas Group B had serum calcium level of 8.01 mg/dl ± 0.98 (p=0.02). Conclusions: The findings underscore the intricate relationship between metabolic disorders and mineral homeostasis, highlighting the potential implications for clinical management and risk stratification in diabetic patients.